INFORMATION ABOUT THE ECONOMIC LIFE OF THE COUNTRY IN THE SECOND HALF OF THE 19TH CENTURY AND THE BEGINNING OF THE 20TH CENTURY IN THE DOCUMENTS OF THE TURKESTAN GENERAL GOVERNOR'S COURT - Ergashev Bakhtiyar Ergashevich (American Journals Publishing, 2023)
Uzbekistan's independent development has created ample opportunities to open new, unexplored areas of scientific research in the field of history. The given article is devoted to the questions of source-studying of the history of Turkestan of the second half of the 19th and the beginning of the 20th centuries. The main sources are the office documents of general-governor of Turkistan on the basic of which the questions of economical life in Samarkand, Syrdarya, Fergana, Semirechensk and Transcaspian regions are taken into consideration.
Keywords: Source-studying of the history of Turkestan, economical life in Samarkand, the office documents of general-governors, agriculture, providing the population with food, urban and rural residents, plant and factory industry, trade.